Human maritime subsistence strategies in the Lesser Sunda Islands during the terminal Pleistocene–early Holocene: New evidence from Alor, Indonesia. (19th September 2016) - Samper Carro, Sofía C.; O'Connor, Sue; Louys, Julien; Hawkins, Stuart; Mahirta, Mahirta
Abstract: The islands of Wallacea are remarkable on a world scale as settlement occurred by at least 43, 000 cal BP and must have involved the use of watercraft. The majority of the islands are depauperate in terrestrial fauna and human subsistence must have focused on the marine environment. Although few islands have been archaeologically explored, some such as Timor have yielded abundant remains of pelagic and reef fishes, as well as the earliest evidence of fishhook manufacture, demonstrating that modern humans in this region were well equipped to undertake complex exploitation of the marine environment. However, a holistic understanding of human subsistence strategies on these islands from initial colonisation in the late Pleistocene through to the Recent remains elusive. Here, we present survey and excavation data from the site of Tron Bon Lei on the small island of Alor in Nusa Tenggara Timur, Indonesia. This study focuses on the terminal Pleistocene – early Holocene human fishing behaviour in the region, and specifically the zooarchaeological sequence from Tron Bon Lei dated to this period. The Holocene preference for reef fish relative to pelagic fish, observed in mid-to late Holocene occupation levels in East Timor, occurred earlier in Tron Bon Lei, suggesting a shift from the larger abundance of carnivore taxa observed in the late Pleistocene deposits. Comparisons with other archaeological deposits in Wallacea indicates that fishing was an important subsistence activity in Nusa Tenggara Timur, unlike more northern Wallacean islands where shellfish make up almost all zooarchaeological records. Tron Bon Lei confirms that the faunally limited nature of Alor spans the Holocene, and we find no evidence that terrestrial fauna made up a significant component of the subsistence activities undertaken at this site.